Waveform analysis of the fetal ECG in labor in patients with intrahepatic cholestasis of pregnancy. Issue 2 (11th September 2018) - Joutsiniemi, Titta; Ekblad, Ulla; Rosén, Karl G.; Timonen, Susanna
Abstract: Aim: Intrahepatic cholestasis of pregnancy (ICP) is reported to be associated with an increased risk of sudden fetal death. The possible mechanism is thought to be cardiac arrhythmia. Prolonged QT interval of the electrocardiogram (ECG) is associated with arrhytmogenic events. The aim of the study was to compare the fetal ECG QT interval during labor in pregnancies complicated with ICP to healthy controls. Methods: The fetal ECG and QT interval was reviewed retrospectively. The intrapartum QT interval was measured in 61 fetuses born to mothers with ICP and in a control group of similar size. The corrected QT interval (QTc) was calculated using Bazett's formula: QT/√RR. The occurrence of ST segment depression was also included in the analysis. Results: The groups were similar regarding to maternal age, parity, BMI, gestational age and smoking habits. The rate of labor induction was significantly higher in ICP patients ( P  < 0.001). The QTc at the beginning and the end of recording was analyzed and there were no significant differences in these values between the ICP patients and healthy controls ( P  = 0.467). Most ICP patients used ursodeoxycholic acid (UDCA) for mediation. We analyzed separately patients who had elevated liver enzymes before labor. No significant differences in the QTc were noted in these patients either. Nor were there any significant ST depressions in ICP patients. Conclusions: The etiology of adverse perinatal outcome and even sudden fetal death in ICP is still controversial. No differences in QTc intervals and ST waveforms during labor were found in our study material.